Analisis Status Pemanfaatan Ikan Swanggi (Prianchantus tayenus) yang Didaratkan di Pelabuhan Perikanan Nusantara (PPN) Brondong, Lamongan Jawa Timur - Reni Maulana; Achmad Kusyairi; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2026)
Swanggi fish (Prianchantus tayenus) is one of the important commodities that are widely caught at the Perikanan Nusantara Port (PPN) Brondong, Lamongan, East Java. Increased fishing acivity is feared to cause excessive pressure on fishery resources that could potentially cause overfishing. This study aims to analyze the level and status of swanggi fish utilization. The method used in this research is descriptive quantitative with a fox production surplus model approach to calculate Maximum Sustainable Yield (MSY), Totl Allowable Catch (TAC), and utilization rate. The data analyzed were the catch abd effort of swanggi fishing from 2015 to 2024. The result showed that the Maximum Sustainable Yield (MSY) value of Swanggi fish was 14,486,042 kg/year with an optimum effort F MSY of 11,689 trips/catch and TAC of 11,588,833 kg. the utilization rate of swanggi fish during 2015 to 2024 reached 105%. The value of the utilization status of swanggi fish is 85% which can be categorized that the exploitation of swanggi fish resources is Full Exploited. Therefore, sustainable fisheries management is needed through effort limitation and gear evaluation to maintain the sustainability of swanggi fish resources in PPN Brondong.